2008
DOI: 10.1039/b812968a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of dopamine using a polysilicon nanowire field-effect transistor

Abstract: An unprecedented high sensitive sensing of neurotransmitter dopamine at fM level was demonstrated using a poly-crystalline silicon nanowire field-effect transistor (poly-SiNW FET) fabricated by employing a simple and low-cost poly-Si sidewall spacer technique, which was compatible with current commercial semiconductor processes for large-scale standard manufacture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 32 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…Recently, the dopamine detection by using ion-sensitive FET devices modified with phenylboronic acid has been reported (Freeman et al, 2007). An ultrasensitive dopamine FET sensor based on polysilicon nanowires has been demonstrated as well (Lin et al, 2008). However, to the best of our knowledge, the utilization of organic thin film transistor (OTFT) for dopamine detection has not been investigated up to date.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the dopamine detection by using ion-sensitive FET devices modified with phenylboronic acid has been reported (Freeman et al, 2007). An ultrasensitive dopamine FET sensor based on polysilicon nanowires has been demonstrated as well (Lin et al, 2008). However, to the best of our knowledge, the utilization of organic thin film transistor (OTFT) for dopamine detection has not been investigated up to date.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, interferences and selectivity still need to be checked from a practical point of view for the selective detection of small compounds using CNTFET devices. Silicon nanowires fieldeffect transistors, which are closely related to CNTFET devices, have been also successfully used for detecting small molecules such as calcium ions (Bi et al, 2008) or dopamine (Lin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, several studies have used NWFET-based biosensors for label-free, ultra-high-sensitivity, and real-time detection of various biological targets, including a single virus 2 , adenosine triphosphate and kinase binding 3 , neuronal signals 4 , metal ions 5,6 , bacterial toxins 7 , dopamine 8 , DNA [9][10][11] , RNA 12,13 , enzyme and cancer biomarkers [14][15][16][17][18][19] , human hormones 20 , and cytokines 21,22 . These studies have demonstrated that NWFET-based biosensors represent a powerful detection platform for a broad range of biological and chemical species in a solution.…”
Section: Introductionmentioning
confidence: 99%